Online Learning Experiments and Experiences through Google Groups: A Case of M.A. Education Programme of IGNOU during Covid-19 Pandemic - Dey, Niradhar (Indian Journal of Educational Technology, 2022)
This paper is on online Google Groups of the first year learners of the M.A. Education programme of IGNOU who has enrolled in the January 2020 session. During the Covid-19 Pandemic lockdown period, it was difficult to continue the regular curriculum transaction strategy of the programme. It is therefore, an online Google Group for the learners was specially created for providing programme-related information, induction to the programme, addressing various support services and learning needs of the learners as well as to acquainting them with many operational issues. It was thought to use the online Google Groups platform as their number was huge, i.e. 1452 and they were spread across India in almost all the Regional Centres and also in a few overseas centres. The online Google Group was started on 30th March 2020. The article has been prepared based upon the two week experience of the programme coordinator on operating the Google group, i.e. from 1-15 April 2020. In a single platform of online Google Groups, individual learner queries, various support services and the learning needs of the newly enrolled learners have been addressed very successfully. Data revealed that the learners had successfully accessed the hyperlinks based documents like Self Learning Materials (SLMs), Assignment Questions, PowerPoint presentations, Audio-Video Materials, Term End Examination question papers, Teleconferencing & Interactive Radio Counselling sessions, and have also acquainted themselves with many other operational issues of the programme by using the online Google Groups. In practice of only two weeks through the online Google Groups, this has been realised that the learners had successfully acquainted with the programme and had engaged in studies like writing their assignment responses, participated in discussion forums on various themes and also engaged in peer and group learning processes. It was no doubt a successful experiment of the programme during the Covid-19 Pandemic period and also an eye-opener for the programme coordinators to make it an important part of programme transaction for the future.